2009
DOI: 10.1556/aagr.57.2009.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Differences in staining of the unicellular algae Chlorococcales as a function of algaenan content

Abstract: Algal strains belonging to the Chlorococcales (Chlorophyceae) show significant differences in the extent of staining with the commonly used dye, crystalline violet. This seems to depend on the cell wall composition and on the occurrence of the acetolysis-resistant biopolymer algaenan in the algal cells.Eighteen algal strains were investigated using 24 h staining with 0.2% crystalline violet and it was confirmed that algal strains which did not contain algaenan and had a trilaminar structure in the cell wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…To proof the selection of strains, Crystal Violet, Calcofluor, Ruthenium red, Toluidine blue O and FD4-staining were performed to characterize the investigated coccoid strains with respect to cell wall properties. These findings support the work of Kodner et al (2009) and Zych et al (2009) who showed algaenan as present in the species A. obliquus . Also for D. armatus the presence of algaenan was demonstrated before ( Allard and Templier, 2000 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To proof the selection of strains, Crystal Violet, Calcofluor, Ruthenium red, Toluidine blue O and FD4-staining were performed to characterize the investigated coccoid strains with respect to cell wall properties. These findings support the work of Kodner et al (2009) and Zych et al (2009) who showed algaenan as present in the species A. obliquus . Also for D. armatus the presence of algaenan was demonstrated before ( Allard and Templier, 2000 ).…”
Section: Discussionsupporting
confidence: 92%
“…The investigated species were selected based on literature research for presence or absence of algaenan ( Table 1 ). In addition, cell wall resistance for all investigated green algae was evaluated again by (a) cell inner staining with Crystal Violet, proposed by Zych et al (2009) , Ruthenium red and Toluidine blue O (b) by estimating the ratio of flow cytometrically measured Calcofluor-fluorescence to Forward-Scatter-signal and (c) exemplary flow cytometric detection of accumulated empty cell walls in the culture ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential sensitivity of green algae species to allelopathic effects is often discussed in ecotoxicological studies (Chalifour et al, 2009) and might depend on the cell wall composition. Zych et al (2009) found evidence that the permeability of the cell wall is greater in strains with a tri-laminar structure and which do not contain algaenan. O. marsonii is known to possess a tri-laminar cellulose cell wall (Quader, Robinson & van Kempen, 1983;Fujino & Itoh, 1994;Krienitz & Bock, 2012), whereas S. obliquus contains algaenan in its cell wall (Atkinson, Gunning & John, 1972).…”
Section: Co-cultivation Of M Aeruginosa-o Marsoniimentioning
confidence: 97%